Technical evaluation of selected soil conservation practices and farmers' perception about soil erosion in Donbi Watershed, Wolaita Zone, Southern Ethiopia - Bekele Tsegaye; Moges Awdenegest (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2018)
A study was conducted at Donbi watershed, Wolaita zone, southern Ethiopia to identify, describe and evaluate different introduced soil and water conservation practices and to assess farmers' perceptions about soil erosion and conservation measures. The necessary data were generated through field measurements and structured questionnaire survey, group discussion and transect walk. The structures were evaluated by comparing the field measurement result with the recommended dimensions. The results obtained showed that level soil bund and fanya juu were the dominant structures identified in the watershed. The technical evaluation of the structures showed that generally the spacing of soil bund was wider than the recommended while in most fanya juus within the acceptable range. Similarly, the channel depth of the structure in different parts of the watershed was smaller than the recommended. Farmers in the watershed are aware of the problem of soil erosion and the importance of conserving soil. They have also developed their own judgments about the relationship between different dimensions of bunds and soil erosion as a result of long field experience in their locality.